2022
DOI: 10.3390/microorganisms10061172
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Analysis of Rhodococcus opacus S8 Capable of Degrading Alkanes and Producing Biosurfactant Reveals Its Genetic Adaptation for Crude Oil Decomposition

Abstract: Microorganisms capable of decomposing hydrophobic substrates in cold climates are of considerable interest both in terms of studying adaptive reactions to low temperatures and in terms of their application in biotechnologies for cleaning up oil spills in a crude-oil polluted soil. The aim of this work was to investigate the genome of Rhodococcus opacus S8 and explore behavior traits of this strain grown in the presence of hexadecane. The genome size of strain S8 is 8.78 Mb, of which the chromosome size is 7.75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The transmission electron microscopy observation of ultrathin sections of X5 cells grown on solid hexadecane showed that vesicles were connected to cells by means of electron-dense filaments-fibers (F) (Figure 5). Delegan et al [43] studied the ultrastructure of rhodococci cells grown on dodecane at 28 • C. They described surface fibrillar structures, which are most commonly used by bacterial cells to attach to the surface. In contrast, we showed that fibers were pili-like structures that were hollow and possibly served to transport hexadecane and its intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…The transmission electron microscopy observation of ultrathin sections of X5 cells grown on solid hexadecane showed that vesicles were connected to cells by means of electron-dense filaments-fibers (F) (Figure 5). Delegan et al [43] studied the ultrastructure of rhodococci cells grown on dodecane at 28 • C. They described surface fibrillar structures, which are most commonly used by bacterial cells to attach to the surface. In contrast, we showed that fibers were pili-like structures that were hollow and possibly served to transport hexadecane and its intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the surface tension, the value decreased by up to 46 and 45 mN/m with the B. amyloliquefaciens C11 and S. lavendulae C27 strains, respectively. The values, although high, are in the range of the values of biosurfactants produced by other microorganisms under non-optimized conditions [ 8 , 10 , 13 , 21 ]. The ability to lower the surface tension of aqueous solutions is an important property that characterizes a potent surface-active agent [ 65 ], and according to the literature, a drop in surface tension to under 35 mN/m indicates that the microorganism is an efficient biosurfactant producer [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…These biosurfactants can be applied in a wide variety of productive sectors, such as in the formulation of detergents, cosmetics, body hygiene products, paints and varnishes, agricultural applications, and pharmaceuticals, among others [ 6 ]. An example of an environmental application of biosurfactants is their use in the bioremediation of heavy metals [ 7 ], oil spills [ 8 ], and pesticides [ 9 , 10 ] due to their ability to solubilize hydrophobic compounds through the formation of emulsions that are formed by reducing the surface tension and interfacial tensions between liquids, solids, and gases [ 11 ]. In this process, molecular aggregates (micelles) are formed, which promote mass transfer to the microorganism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strains used in the study were isolated from different sources and characterized as previously described ( Rhodococcus erythropolis X5 25 , Rhodococcus opacus S8 26 , Rhodococcus qingshengii 7B 27 , Rhodococcus qingshengii VT6 28 , Priestia aryabhattai 25 29 , Gordonia amicalis 6-1 30 , Gordonia alkanivorans 135 31,32 , Gordonia polyisoprenivorans 135 33 , Rhodococcus opacus 1CP 34 , Rhodococcus opacus 3D 35 ).…”
Section: Methodsmentioning
confidence: 99%